TAXATION OF OPERATIONS WITH CRYPTOASSETS AND ITS IMPACT ON BUDGET POTENTIAL IN UKRAINE - SEREBRIANSKYI, Dmytro; BIRYUK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The rapid development of crypto assets has led to a transformation in the structure and functioning of individual components of the financial system. On the one hand, new opportunities are opening up for transactions, when payments and other financial services become cheaper, faster, and more accessible. On the other hand, the active use of crypto assets creates problems for financial stability as a result of their replacement of assets and currencies, which has received the name "cryptoization". Understanding and streamlining the processes of cryptoization requires a deeper study of this problem in order to develop tools to influence it.The article assesses the potential budget revenues from taxing income from crypto asset operations. It is determined that the introduction of a modern cryptocurrency taxation system is an extremely important step for maintaining the sustainability and innovation of the financial system in Ukraine. Effective taxation of cryptocurrency operations will contribute to attracting new investments, developing financial innovations and supporting innovative startups, preventing illegal cryptocurrency operations, stable growth of budget revenues, and ultimately - the stability of the financial system. The feasibility of introducing a tax rate of 5% of the profit from cryptocurrency operations is substantiated in order to stimulate cryptocurrency startups and attract investors.The development of taxation of virtual assets should take place in the context of supporting constant financial innovations in conditions of limited information and focusing on ensuring tax flows to the budget. Conceptually, the dual functional nature of cryptocurrencies as investment assets and means of payment creates difficulties in fixing capital gains and losses when used as investment assets. As for the introduction of VAT and sales tax, it is advisable to classify cryptocurrencies similarly to the national currency. The effectiveness of collecting income tax will depend on the technologies for processing information about profits and losses and accounting for cryptocurrency transactions. In Ukraine, effective taxation of virtual assets will allow streamlining the processes of their circulation and ensuring their regulation at the state level, will provide a non-debt method of filling the budget, a more inclusive way of financing the reconstruction and development of the real sector of the economy, will contribute to maintaining the potential for creating capital markets and preserving the innovative nature of the development of the financial system.
Keywords: financial system; cryptoassets; taxation; tax revenues; regulation of circulation of cryptoassets; tokens; cryptoecosystem; cryptoization